Interrelationship of rotavirus infection and Creatine Kinase-MB isoenzyme levels in children hospitalized with acute gastroenteritis in Guangzhou, China, 2012–2015 - Jianbin Zheng (Nature Portfolio, 2017)
Abstract Elevated levels of Creatine Kinase-MB (CK-MB) Isoenzyme are a common phenomenon among rotavirus (RV) diarrhea. However, few studies have addressed this issue using large sample size. In current study, 1,118 children (age <5 years) hospitalized with diarrhea in Guangzhou Women and Children’s Medical Center from 2012 to 2015 were finally included. Changing pattern of CK-MB and its relationship with RV-infection were analyzed and characterized. Multivariate linear regression models showed that RV-positive cases had a 28% rise in CK-MB compared to RV-negative cases (OR = 1.28, 95% CI: 1.15 to 1.41, P < 0.01) after controlling for age, gender, season of admission, and weight. The pattern of change showed that CK-MB level of RV-positive group started to rise immediately at the 1st day of diarrhea, reached the peak on days 2 to 4, declined during 4–9 days, and then reached a relatively stable level when compared to the RV-negative group. Mediation analyses showed that indirect effect of RV infection on the increase of CK-MB via Vesikari score was significant (β = 8.01, P < 0.01), but direct effect was not (β = 9.96, P = 0.12). Thus, elevated CK-MB value is a common finding in RV-infection and completely mediated by the severity of diarrhea. CK-MB monitoring may help to identify children with more severe viral infection.